2017
DOI: 10.2903/j.efsa.2017.5018
|View full text |Cite
|
Sign up to set email alerts
|

Avian influenza overview October 2016–August 2017

Abstract: The A(H5N8) highly pathogenic avian influenza (HPAI) epidemic occurred in 29 European countries in 2016/2017 and has been the largest ever recorded in the EU in terms of number of poultry outbreaks, geographical extent and number of dead wild birds. Multiple primary incursions temporally related with all major poultry sectors affected but secondary spread was most commonly associated with domestic waterfowl species. A massive effort of all the affected EU Member States (MSs) allowed a descriptive epidemiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 122 publications
1
40
0
Order By: Relevance
“…These outbreaks required ≈25 million poultry to be destroyed or culled as part of preventive action ( 30 ). According to the EU reference laboratory for avian influenza, as October 4, 2017, EU Member States had reported 2,781 outbreaks of H5N8 influenza in poultry, wild birds, and captive birds, as well as 20 outbreaks of H5N5 influenza and 1 outbreak of H5N6 influenza in a wild bird ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These outbreaks required ≈25 million poultry to be destroyed or culled as part of preventive action ( 30 ). According to the EU reference laboratory for avian influenza, as October 4, 2017, EU Member States had reported 2,781 outbreaks of H5N8 influenza in poultry, wild birds, and captive birds, as well as 20 outbreaks of H5N5 influenza and 1 outbreak of H5N6 influenza in a wild bird ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Different responsibilities between these authorities and local, regional, and national levels hampered comprehensive information about numbers of persons exposed. Only 9 countries were able to provide at least some veterinary data, which suggested that ≈1,570 persons were exposed during 258 outbreaks ( 30 ). The total number of exposed persons or exposure events during outbreaks in all affected countries remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The European Food Safety Authority (EFSA) asked all EU/EEA countries’ representatives to provide data on HPAI outbreaks for the period October 2016–June 2017 (Brown, Mulatti, et al ()). Reporting categories included the number of susceptible birds, holding specifications (commercial, non‐commercial) and the number of people exposed.…”
Section: The Studymentioning
confidence: 99%
“…Between 2016 and 2018, outbreaks of highly pathogenic avian influenza virus (HPAI) A(H5N8), A(H5N6) and A(H5N5) affected 24 EU/EEA countries (EFSA, Brown, Kuiken, et al ; EFSA, Brown, Mulatti, et al, ). Approximately 20 million birds had to be culled either directly due to a confirmed outbreak or indirectly as a precaution, for example, related to prevention measures within the control zone (Hansen, Brown, Brookes, Welchman, & Cromie, ; Napp, Majo, Sanchez‐Gonzalez, & Vergara‐Alert, ).…”
Section: Introductionmentioning
confidence: 99%
“…Since September 2017 EFSA, working in close collaboration with the ECDC and the EURL, has released five scientific reports updating on the AI situation within Europe and worldwide (EFSA 2017a;2017b;2018a;2018b;2018c). Each of these reports covered a three month period update (September to November 2017, November 2017 to February 2018, February to May 2018, and May to August 2018), with the exception of the first report that provided an update for the time period between October 2016 and August 2017.…”
mentioning
confidence: 99%